Greenhouse gas emission on Brazilian beef production: from experimental data to farm-scale modeling - Mazzetto, André Mancebo (2014)
The emission of greenhouse gases (GHG) is currently intensely debated issue. Countries with reduction targets of GHG emissions have developed studies to understand the processes and reduce the emissions. Farming is the main source of GHG emissions in Brazil. Among the main products of Brazilian agriculture is cattle, handled mainly in the extensive system, where animals are slaughtered at an average of three to four years and grassland receives little or no cultural tract. Quantification and monitoring of GHG emissions in agricultural systems enable the evaluation of the degree of impact on the environment. This thesis discussed the main sources of greenhouse gases emissions in animal husbandry and the guidelines on research to evaluate alternative sustainable systems of beef production. The main results are the emission factors for tropical conditions from various sources, such as faeces (Chapter 3) and urine (Chapter 4) from the animals, as well as the application of nitrogen fertilizer and lime on pasture (Chapter 5). The climate proved to be a key factor in the control of greenhouse gases, mainly methane (CH4) from the faeces of animals. The emission factors obtained for cattle faeces were 0.03 and 0.08 kg CH4 head-1 year-1 (average) for subtropical and tropical climates, respectively. The use of a generic emission factor in Brazil is not the best option. More studies are needed in different regions to determine the impact of climate on GHG emissions. The emission factor for nitrous oxide (N2O) from urine was 0.25 % of total N applied (average), significantly lower than the default factor recommended by the IPCC. The use of nitrification inhibitors under tropical conditions is not recommended, since there were no positive results in reducing the emission of N2O from urine. The use of nitrogen fertilizer led to high N2O emissions, however, the dry matter production of forage also increased with fertilizer application. The balance between dry matter production and N2O emission shows that the application of nitrogen fertilizer can contribute significantly to reducing pasture area, with a total reduction of up to 40 %. Mathematical modeling of the data was also performed, simulating beef production under extensive management in different scenarios for the studied area (Chapter 6). The CH4 emission decreased, while the emission of carbon dioxide (CO2) and N2O increased due to the simulated intensification. The simulation showed that the intensification in beef production results in lower GHG emissions per kg of beef. Reductions may reach 2 to 57%, depending on the scenario. The intensification also contributes to the reduction of the total area and length of the production cycle. These results show that the intensification practices are a potential mitigation option for the beef sector